Writing A Scientific Paper: Steps And Methods - Hamouda, Abida (Journal of Architecture and environment of child, 2023)
This paper discusses the important steps to take into consideration when writing a scientific article in the field of (AUMV): architecture, urban planning and city trades. It gives the general structure of an article and the way to write its different sections starting with the introduction going through the body of the text: methodology, results and discussion, to end with a conclusion. Apart from the widely used IMRAD method recommended by most journals, an attempt has been made to give some examples of article structure methods. We have tried through this paper to give the recommendations to be taken into consideration for a successful scientific writing that allows to highlight the results of any research.Through this paper we have tried to meet the expectations of doctoral students and facilitate their access to publication and the paths to take to succeed in its writing and submission.